Mitotic Inhibition of GRASP65 Organelle Tethering Involves Polo-like Kinase 1 (PLK1) Phosphorylation Proximate to an Internal PDZ Ligand - Sengupta, Debrup (American Society for Biochemistry and Molecular Biology, 2010)
GRASP65 links cis-Golgi cisternae via a homotypic, N-terminal PDZ interaction, and its mitotic phosphorylation disrupts this activity. Neither the identity of the PDZ ligand involved in the GRASP65 self-interaction nor the mechanism by which phosphorylation inhibits its interaction is known. Phospho-mimetic mutation of known cyclin-dependent kinase 1/cyclin B sites, all of which are in the C-terminal “regulatory domain” of the molecule, failed to block organelle tethering. However, we identified a site phosphorylated by Polo-like kinase 1 (PLK1) in the GRASP65 N-terminal domain for which mutation to aspartic acid blocked tethering and alanine substitution prevented mitotic Golgi unlinking. Further, using interaction assays, we discovered an internal PDZ ligand adjacent to the PLK phosphorylation site that was required for tethering. These results reveal the mechanism of phosphoinhibition as direct inhibition by PLK1 of the PDZ ligand underlying the GRASP65 self-interaction.